Storytelling Morality: Ecofeminism, Agrarianism, and Pigs in the Field - Goralnik, Lissy; Thorp, Laurie; Rozeboom, Dale; Thompson, Paul (The Trumpeter, 2014)
Understanding our relationships with and obligations to the natural world through the labor and practice of food production is central to our development as moral beings and environmental citizens. Both ecofeminism and agrarianism—in their overlap and distance—can offer ideas about how best to express our environmental and citizenship ethics through the everyday act of growing, eating, and engaging with food. Raymond Anthony (2009) reminds us that a narrative ethics approach—embraced by both ecofeminism and agrarianism as a meaningful source of ethical wisdom—when applied to animal agriculture helps to build a more inclusive moral community. But Anthony cautions that the predominant agricultural storyline is made up of incompatible camps. He proposes a new story for agriculture, one that offers reconciliation or revitalization. In the spirit of this revitalization, we offer two stories of our material practice of raising pigs on an educational organic farm to illuminate what we see as important ethical, social, and environmental context for our new agricultural narrative. Through these stories we aim to give context to the theoretical ecofeminist and agrarian dialogue about ethics rooted in the land, so we might better understand what appropriate relationships with nonhuman others and natural systems might look like in practice.